INTEGRATED APPROACH TO ANALYSING THE RELATIONSHIP BETWEEN FACTORS, WORKING CONDITIONS, AND PERFORMANCE INDICATORS IN THE FOREIGN MARKET ENTRY OF RUSSIAN SMES - T. A. Gileva (Стратегические решения и риск-менеджмент)
The article discusses the decision-making strategies of Russian small and medium-sized enterprises (SMEs) when entering foreign markets entry and analyses the factors and conditions that influence the effectiveness of their export activities. It focuses primarily on the analysis of internal and external factors, including sanctions restrictions, access to financial resources, production capacity, marketing skills, digital technologies, and others. Different approaches to factor and condition analysis are discussed, such as the rapid start model, the traditional market entry model, and capture and expansion strategies. It also examines methods for assessing export efficiency, both quantitative and qualitative. The result is a landscape of quality models linking factors and working conditions to the performance of Russian export-oriented SMEs, comprising four primary models, is created.